1994
DOI: 10.1093/mutage/9.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Marked antimutagenic potential of aqueous green tea extracts: mechanism of action

Abstract: In the present study aqueous extracts of green tea, at the concentrations customarily consumed by humans, were evaluated for their antimutagenic activity against major classes of dietary and occupational carcinogens. Green tea extracts caused a very marked and concentration-dependent inhibition of the Aroclor 1254-hepatic S9-mediated mutagenicity of heterocyclic amines (IQ and Glu-P-1) and polycyclic aromatic hydrocarbons (benzo[a]pyrene and 7,12-dimethylbenz[a]anthracene) and of the isoniazid-induced S9-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…The latter should augment rather than diminish HCAs genotoxicity by increased HCAs bioactivation ratio to highly reactive arylnitrenium intermediates, suggesting that mechanisms other than the modulation of phase I enzymes can be involved in observed protective action. The inhibitory effects of tea extracts towards promutagens (IQ, Glu-P-1) as well as directacting mutagens (9-aminoacridine and N-methyl-N-nitro-N-nitrosoguanidine) further support the hypothesis that protective effects of CAF cannot be fully explained by its influence on xenobiotic activation system [80]. The presence of mechanisms additional to the inhibition of cytochrome P450 enzymatic activity was also suggested by Chen and Yen [73].…”
Section: Inhibition Of Hcas Activity By Cafsupporting
confidence: 52%
“…The latter should augment rather than diminish HCAs genotoxicity by increased HCAs bioactivation ratio to highly reactive arylnitrenium intermediates, suggesting that mechanisms other than the modulation of phase I enzymes can be involved in observed protective action. The inhibitory effects of tea extracts towards promutagens (IQ, Glu-P-1) as well as directacting mutagens (9-aminoacridine and N-methyl-N-nitro-N-nitrosoguanidine) further support the hypothesis that protective effects of CAF cannot be fully explained by its influence on xenobiotic activation system [80]. The presence of mechanisms additional to the inhibition of cytochrome P450 enzymatic activity was also suggested by Chen and Yen [73].…”
Section: Inhibition Of Hcas Activity By Cafsupporting
confidence: 52%
“…Overall, it may be concluded from these studies that components other than the Ña-vanols are the major antimutagenic components present in green tea. A combination of two mechanisms, namely inhibition of the cytochrome P450 isoforms involved in the bioactivation of carcinogens and trapping of genotoxic metabolites are responsible for the antimutagenic activity of green tea (Bu-Abbas et al 1994). It is possible that Ñavanols play a role in only one of these two mechanisms, thus explaining the lack of correlation between antimutagenic potential of the tea fractions and Ñavanol content.…”
Section: Discussionmentioning
confidence: 99%
“…Microsomal metabolism was terminated by the addition of 100 kl of menadione (900 kM) and a second 20 min preincubation was carried out. Menadione is a potent inhibitor of the NADPH-dependent bioactivation of chemical carcinogens (Bu-Abbas et al 1994). Top agar was added and the mixture was poured onto minimal agar plates which were incubated for 48 h at 37¡C to allow revertants to develop into colonies.…”
Section: Evaluation Of the Mutagenic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang (Wang et al, 1989) suggested green tea polyphenols have a significant anti-skin tumour initiating activity when tested against polycyclic aromatic hydrocarbons in mice. Catechins possess antimutagenic activities (Bu-Abbas et al, 1994), and anti-genotoxic effects (Sugisawa et al, 2004), induce apoptosis in cancer cells (Hayakawa et al, 2001), and inhibit angiogenesis (Jung et al, 2001) that makes them useful as anti-carcinogenic compounds. In epithelial tumours, the epidermal growth factor receptor (EGFR) is highly expressed and is inhibited by EGCG (Masuda et al, 2001;Shimizu et al, 2005).…”
Section: Cancermentioning
confidence: 99%